Pengalaman Kader Kesehatan dalam Penanggulangan COVID-19 di Kabupaten Kendal, Jawa Tengah - Andika Mirza Fahriyan; Yulian, Vinami (EDUPEDIA Publisher, 2023)
Objective: This research aims to determine the experience and role of health cadres in dealing with the COVID-19 pandemic. Methods: This research uses a qualitative research method with an exploratory approach. The number of participants in this research was six health cadres using a purposive sampling approach. The data collection technique in this research used interviews. Results: After carrying out the thematic analysis process, three themes were found from the results of the in-depth interviews, namely (1) The role of health cadres in dealing with COVID-19, (2) Factors that make it easier for cadres to deal with COVID-19, and (3) Factors that hinder cadres in dealing with COVID-19. Conclusion: Health cadres are aware of their role and responsibility in dealing with COVID-19 in society. Health cadres have a role as mobilizers and supervise the community in complying with health protocols. However, in carrying out their role, many health cadres receive unpleasant treatment, namely in the form of rejection and discrimination from the community and local government assistance is still lacking.